On the problem of optimal structure design subjected to regular lifetime criterion - Nguyen Van Pho (Vietnam Journal of Mechanics)
The objective function of problem of optimal structure design can be chosen differently. For example the objective function can be the weight, the net cost, the regular resistance, the regular reliability, an so on.